Dynamics of civil structures. proceedings of the 38th IMAC, a Conference and Exposition on Structural Dynamics 2020 /: proceedings of the 38th IMAC, a Conference and Exposition on Structural Dynamics 2020. Volume 2 : (2020) - Unknown
No abstract available